Functionalized silicon dioxide self-referenced plasmonic chip as point-of-care biosensor for stroke biomarkers NT-proBNP and S100β - Koh, Brescia (2021)
Surface plasmon resonance (SPR) biosensors are often used in the detection of solid, liquid or gaseous samples in diagnostics, pharmaceutics and military defense. Plasmon waveguide resonance (PWR) mode is obtained when a dielectric waveguide layer is added to the metal film. In this study, a self-referenced PWR (SRPWR) silicon dioxide (SiO₂) chip was examined. The self-referenced measurement is important to compensate for temperature fluctuations, other instabilities and allows RI signal measurement without an additional reference sample, thus minimising the sample volume needed. The chip was fabricated with a multi-layer of metals and dielectrics, consisting of a 420 nm SiO₂ layer, a 40 nm Ag layer and another 480 nm SiO₂ layer. This chip was shown to give one internal plasmon excited on the bottom interface SiO₂/Ag, which is used as self-reference in the detection. The top layer acts as a waveguide layer and can be designed to give modes with ultrahigh penetration depth. A direct assay was developed, where the recognition molecule (specific antibody) was immobilized onto the SiO₂ plasmonic chip surface, via a covalent coupling protocol based on 3-aminopropyltriethoxysilane (APTES) and glutaraldehyde. The SRPWR biosensor was developed for the sensing of two chosen stroke biomarkers: NT-proBNP and S100β, which are sensitive and specific for stroke diagnostics. For both biomarkers, a linear decreasing pattern in the RI signal was recognized with the increasing biomarkers concentrations. Biomarkers detection was conducted in deionized water and validation was done in spiked porcine plasma. The SiO₂ based plasmonic chip demonstrates a limit-of-detection of less than 1 ng/mL that is clinically relevant for both stroke biomarkers.